新加坡华语语言使用的性别差异 ：以综艺节目为例 = Gender difference in Singapore Mandarin Chinese : a study based on local variety shows in Singapore - 姚可嘉 Yow, Ke Jia (Nanyang Technological University, 2020)
性别是影响语言变体的因素之一。本文以综艺节目为例，探讨新加坡在华语语言使用上的性别差异。本文主要从语码转换、感叹词和语气词，以及附加问句，三个层面来分别探讨语言使用的性别差异，并且讨论造成性别差异的原因以及其发展趋势。本文发现无论是在语码转换、感叹词和语气词还是附加问句的角度，男女在语言使用上都存在着一定的差异，并进一步探讨导致这些差异的可能因素。本文也指出随着时代的进步，男女在说话上的差异会逐渐缩小。Gender is one of the factors that lead to variation in languages. With the data from Singapore local variety shows, this study aims to investigate the gender difference in Singapore Mandarin Chinese, from three aspects, including code-switching, interjections and tag questions.The results of this study showed that men and women exhibit certain differences in all three aspects, and further discusses the possible factors that may have contributed to the differences. This study also argues that as time progresses, gender difference in language use will reduce gradually.